Seismic Performance and Strengthening of Purlin Roof Structures Using a Novel Damping-Limit Device - Chen, Baokui; Jia, Bao; Wen, Ming; Li, Xiaodong (Frontiers in Materials, 2021)
Purlin roof structure houses, which have the advantages of readily accessible materials and simple construction, are widely used in rural areas of China. However, during earthquakes, the wooden purlins tend to fall off and the walls crack. Therefore, it is necessary to monitor the structural parameters of and strengthen the anti-seismic capacity of these structures. To compensate for the seismic deficiencies of the purlin roof structure, a novel damping-limit device installed at the connection position of the gable and the wooden purlin was proposed. In this study, the seismic performance and reinforcement effect of the brick-wood structure with the purlin roof were analyzed through numerical simulation. The research results indicate that the novel damping-limit device proposed in this study can significantly reduce the local stress concentration and the seismic response of the structure, and thereby rectifying the seismic defect of falling purlin. Moreover, compared with the traditional strengthening method, the novel device is more convenient to install and the reinforcement quality is easier to ensure.